Nurse Managers' Leadership Styles in Turkey: Literature Review - Hülya Yılmaz; Filiz Kantek (Association of Nurse Managers, 2016)
BACKGROUND: Nurse managers have to show leadership behaviours because of complex technology and intensive human relations taking place in nursing services. AIM: The objective of the study is to reveal the current situation and identify the needs in this area by examining studies about nurse managers' leadership styles in Turkey. METHOD: Literature scanning method was used in this study. In order to access into studies; Turkish Medical Index, Akdeniz University library database, Google Academic, YOK Thesis Scanning Centre, Pubmed, EBSCO Host and Web of Science database were screened. 'Leadership', 'Nurse' and 'Turkey' keywords were used both in Turkish and English languages while the search was being carried out. It was found that eleven studies were fulfilling the inclusion criteria. FINDINGS: It was determined that most of the studies about nurse managers' leadership style in Turkey were done as descriptive studies in Istanbul and in the year 2006. Nurse managers are determined to adopt more business-oriented leadership style. CONCLUSION: It has been revealed that studies about nurse managers' leadership styles in Turkey are limited in number and more work on this issue are needed to be done. Furthermore, it is considered that nurse managers' transformational leadership style must be developed.